The Meaning of {pqdwn} in the Nabataean Inscription of Qabr at-Turkmān - Conklin, Blane W. (Journal of Semitic studies, 2004)
Until 1959, the word {pqdwn} in the Turkmāniyeh inscription was universally understood to mean something like ‘order’ or ‘command’. Then J. Milik suggested that it means ‘responsibility’, which in this context gave the sentence a completely different meaning, and this interpretation has held the day ever since. This article demonstrates that the older understanding of this word is the correct one in this context, based on the word's usage in Jewish Aramaic and Syriac and upon the content of grave inscriptions in general. There are no other attestations of the word in Nabataean itself. In addition, the author proposes an alternate analysis of the syntax of the sentence in which {pqdwn} occurs, which yields a better understanding of the meaning of the text.